2‐Substituted thienotetrahydropyridine derivatives: Allosteric ectonucleotidase inhibitors. Issue 12 (26th October 2021) - Schäkel, Laura; Mirza, Salahuddin; Pietsch, Markus; Lee, Sang‐Yong; Keuler, Tim; Sylvester, Katharina; Pelletier, Julie; Sévigny, Jean; Pillaiyar, Thanigaimalai; Namasivayam, Vigneshwaran; Gütschow, Michael; Müller, Christa E.
Abstract: The antithrombotic prodrugs ticlopidine and clopidogrel are thienotetrahydro‐pyridine derivatives that are metabolized in the liver to produce thiols that irreversibly block adenosine diphosphate (ADP)‐activated P2Y12 receptors on thrombocytes. In their native, nonmetabolized form, both drugs were reported to act as inhibitors of ectonucleoside triphosphate diphosphohydrolase‐1 (NTPDase1, CD39). CD39 catalyzes the extracellular hydrolysis of nucleoside tri‐ and diphosphates, mainly adenosine 5ʹ‐triphosphate (ATP) and ADP, yielding adenosine monophosphate, which is further hydrolyzed by ecto‐5ʹ‐nucleotidase (CD73) to produce adenosine. While ATP has proinflammatory effects, adenosine is a potent anti‐inflammatory, immunosuppressive agent. Inhibitors of CD39 and CD73 have potential as novel checkpoint inhibitors for the immunotherapy of cancer and infection. In the present study, we investigated 2‐substituted thienotetrahydropyridine derivatives, structurally related to ticlopidine, as CD39 inhibitors. Due to their substituent on the 2‐position, they will not be metabolically transformed into reactive thiols and can, therefore, be expected to be devoid of P2Y12 receptor‐antagonistic activity in vivo . Several of the investigated 2‐substituted thienotetrahydropyridine derivatives showed concentration‐dependent inhibition of CD39. The most potent derivative, 32, showed similar CD39‐inhibitory potency to ticlopidine, both acting as allosteric inhibitors. Compound 32 showed an improved selectivity profile: While ticlopidine blocked several NTPDase isoenzymes, 32 was characterized as a novel dual inhibitor of CD39 and CD73. Abstract : Ectonucleotidase inhibitors lead to an increased extracellular concentration of proinflammatory, antiproliferative adenosine 5ʹ‐triphosphate (ATP) while reducing the levels of the immunosuppressive adenosine. Derivatives of the antithrombotic prodrug ticlopidine, in which the 2‐position was blocked to prevent oxidative bioactivation, were identified as inhibitors of the ATP‐hydrolyzing ectoenzyme CD39. They possess potential as novel lead structures in drug development.